Geology of Kulim-Baling Transect with Emphasis on Depositional Environment - Bin Mohd Roslim, Ku Muhammad Nur Azmi (Universiti Teknologi PETRONAS, 2015)
Within the study area between Kulim-Baling, specifically the roadcut from Tawar to Baling, the deep marine rock units of the Semanggol and Baling Formation show that three different rock units; Rhythmite Member unit and chert unit, which both from the same Semanggol Formation meanwhile the third one is Baling limestone. Both formations are not belong to the same age; Semanggol Formation is belong to Triassic age, which is younger than Baling Formation (Early Silurian). One section of from the study area shows three different facies types, which characterized and differentiated by grain fabric, bed thickness and sedimentary structures. The main three facies types consist of mudstone (F1), massive to faintly laminated sandstone (F2) and sandstone interbedded with mudstone (F3). This study includes the study of sedimentology, petrography and geochemistry of the study area. Four samples from different localities were taken and gathered to determine their lithology and construct geological map (Figure 7). Another samples of carbonaceous materials from Facies 1 (mudstone) were also collected for geochemistry analysis.